Bexarotene Impairs Cognition and Produces Hypothyroidism in a Mouse Model of Down Syndrome and Alzheimer's Disease - Verónica Vidal; Alba Puente; Susana García-Cerro; Susana García-Cerro; María Teresa García Unzueta; Noemí Rueda; Javier Riancho; Javier Riancho; Javier Riancho; Carmen Martínez-Cué (Frontiers Media S.A., 2021)
All individuals with Down syndrome (DS) eventually develop Alzheimer's disease (AD) neuropathology, including neurodegeneration, increases in β-amyloid (Aβ) expression, and aggregation and neurofibrillary tangles, between the third and fourth decade of their lives. There is currently no effective treatment to prevent AD neuropathology and the associated cognitive degeneration in DS patients. Due to evidence that the accumulation of Aβ aggregates in the brain produces the neurodegenerative cascade characteristic of AD, many strategies which promote the clearance of Aβ peptides have been assessed as potential therapeutics for this disease. Bexarotene, a member of a subclass of retinoids that selectively activates retinoid receptors, modulates several pathways essential for cognitive performance and Aβ clearance. Consequently, bexarotene might be a good candidate to treat AD-associated neuropathology. However, the effects of bexarotene treatment in AD remain controversial. In the present study, we aimed to elucidate whether chronic bexarotene treatment administered to the most commonly used murine model of DS, the Ts65Dn (TS) mouse could reduce Aβ expression in their brains and improve their cognitive abilities. Chronic administration of bexarotene to aged TS mice and their CO littermates for 9 weeks diminished the reference, working, and spatial learning and memory of TS mice, and the spatial memory of CO mice in the Morris water maze. This treatment also produced marked hypoactivity in the plus maze, open field, and hole board tests in TS mice, and in the open field and hole board tests in CO mice. Administration of bexarotene reduced the expression of Aβ1-40, but not of Aβ1-42, in the hippocampi of TS mice. Finally, bexarotene increased Thyroid-stimulating hormone levels in TS mice and reduced Thyroid-stimulating hormone levels in CO mice, while animals of both karyotypes displayed reduced thyroxine levels after bexarotene administration. The bexarotene-induced hypothyroidism could be responsible for the hypoactivity of TS and CO mice and their diminished performance in the Morris water maze. Together, these results do not provide support for the use of bexarotene as a potential treatment of AD neuropathology in the DS population.